Analysis of Factors Causing Student Tardiness and Its Mitigation Efforts in Senior High School - Iryas, Nabilla Endmal Putri; Wangkawati, Yustia Syalaisha; Lestari, Jihan Muji; Zen, Ella faridati; Anggraeni, Talitha Syahda (Proceedings Series of Educational Studies, 2024)
Tardiness is a common issue within educational settings, often exhibited by students who trivialize this habit and continue to practice it without considering its repercussions. They prioritize their desire to remain idle. This study aims to determine: (1) the patterns of tardiness behavior among students at SMA Widyagama Malang, (2) the factors contributing to tardiness among these students, and (3) the school’s measures in handling tardy students. This qualitative research employs a case study design, with subjects comprising four students from SMA Widyagama Malang who frequently exhibit tardiness or truancy. Purposive sampling was used to select the subjects. Data collection methods included interviews and observations. The findings from the four subjects indicate persistent daily tardiness driven by laziness, lack of motivation, and a disinterest in attending school, compounded by insufficient parental involvement in their educational activities. The causes of their tardiness are both internal and external, including personal inclinations and parental responses, which perpetuate this behavior. These findings suggest that addressing student tardiness requires focusing on both internal and external factors. Keywords: discipline; tardiness; intervention